Design of the main racetrack microtron accelerator end magnets of the Institute of Physics of University of São Paulo - Kassab, L. R P [UNESP]; Martins, M. N.; Takahashi, J.; Gouffon, P. (My University, 1999)
This work deals with the design of the Institute of Physics of the University of São Paulo (IFUSP) main racetrack microtron accelerator end magnets. This is the last stage of acceleration, comprised of an accelerating section (1.04 m) and two end magnets (0.1585 T), in which a 5.10 MeV beam, produced by a racetrack microtron booster has its energy raised up to 31.15 MeV after 28 accelerations. POISSON code was used to give the final configuration that includes auxiliary pole pieces (clamps) and auxiliary homogenizing gaps. The clamps create a reverse fringe field region and avoid the vertical defocusing and the horizontal displacement of the beam produced by extended fringe fields; PTRACE code was used to perform the trajectory calculations in the fringe field region. The auxiliary homogenizing gaps improve the field uniformity as they create a magnetic shower that provides uniformity of ±0.3%, before the introduction of the correcting coils that will be attached to the pole faces. This method of correction, used in the IFUSP racetrack microtron booster magnets, enabled uniformity of ±0.001% in an average field of 0.1 T and will also be employed for these end magnets. © 1999 The American Physical Society.